Advances in Rolling Circle Amplification (RCA)‐Based DNA‐Functional Materials for Cancer Diagnosis and Therapy - Xun You; Jing Wang; Xiaocui Guo; Dayong Yang (Advanced NanoBiomed Research, 2024)
Developing biocompatible material systems with accurate functional designability and powerful integration capability is the urgent demand of efficient cancer diagnosis and therapy. Deoxyribonucleic acids (DNAs) as biomacromolecules are characterized with sequence programmability, rich biological activity, and molecular recognition, and show great performance in the fabrication of biomedical materials. Rolling circle amplification (RCA) is an efficient isothermal enzymatic amplification strategy for production of ultralong single‐stranded DNA (ssDNA) with defined repeat sequences and structures. By virtue of rational design of the RCA templates sequences, the produced ssDNA enables to integrate and amplify the required function modules, which endows RCA‐based DNA materials with extraordinary performance in cancer therapeutics. In this review, RCA‐based strategies for integration of functional modules are systematically summarized; construction of RCA‐based functional DNA materials and their recent progress in cancer therapeutics including detection, bioimaging, and therapy are overviewed; and finally the opportunities and challenges of RCA‐based assembly strategy in terms of material construction and applications in cancer diagnosis and therapy are discussed. It is envisioned that RCA‐based DNA‐functional materials will provide typical paradigms for the application of DNA‐functional materials in the field of cancer therapeutics, and hopefully provide more possibilities for precision medicine.